Pengaruh Kualitas Layanan Internet Banking terhadap Kepuasan Nasabah pada PT Bank Negara Indonesia Persero Tbk KC Madiun - Febri Nur Endah Safitri (Universitas PGRI Madiun, 2018)
This research has purpose to know the quality of internet banking service in PT BNI Persero Tbk KC Madin, to know customer satisfaction at PT BNI Persero Tbk KC Madiun. In this study the population consists of 512 customers with a sample of 225 clients taken with Incidental sampling technique. Technique of taking data taken by questionnaire, observation and documentation. The analysis was processed with SPSS version 20.0 using simple linear regression with hypothesis test, determination test and t test. The result of the research shows that the result of Simple Linear Regression Test is Y = 12,646 + 0,635 X, constant equal to 12,646 meaning if variable of Quality of Internet Banking Service is fixed then Customer Satisfaction amount is 0,635 so there is influence between Quality of Internet Banking Service to Customer Satisfaction. The result of Coefficient of Determination Adjust (R2) is known 0,377 means 37,7% Quality of Internet Banking Service influenced by Customer Satisfaction, while the rest 62,3% Quality of Internet Banking Service influenced by other variable not examined in this research. The result of t test is t_hitung value is 11,697 while t_tabel is 1,651. This means that the value of 〖t〗 _count> t_table (11,697> 1,651). so it can be concluded that Ho is rejected and Ha accepted.